Study of The Application of Digital Literacy in The Frame of The Independent Curriculum Towards 21st Century Skills in Border Area Students - Jewarut, Siprianus; Dinata Alnija , Marianus; Lidya Sumarni , Margaretha (Mudir : Jurnal Manajemen Pendidikan, 2023)
The purpose of this study was to determine the level of application of digital literacy in schools in the context of implementing an independent curriculum towards 21st century skills for students in border areas. The research was conducted through a combination of qualitative research methods with case study analysis. The stages of the research were carried out by gathering the data obtained through the distribution of questionnaires, interviews and field observations and then presented in a descriptive manner. The distribution of the questionnaire was carried out on June 8, 2023, while observations and interviews were carried out on June 15 and 16, 2023. The research was conducted on grade 4 and 5 students at SDN 01 Bengkayang, West Kalimantan, in the border area, with 45 students as respondents. The results of data acquisition through questionnaires, observations and interviews show that the integration of digital literacy in the implementation of the independent curriculum has been carried out in schools, in the evidentiary questionnaire can be seen in answers no. 8-10 with an average percentage, agree 70.00%. The effectiveness of implementing the integration of digital literacy and the independent curriculum can be seen from the level of students' understanding of questions no. 1-3 with an average percentage of 75.00% agree. Meanwhile, regarding the availability of supporting facilities in the successful implementation of the independent curriculum, especially the process of integrating digital literacy and their campus, the respondents' answers showed that they were still inadequate with a percentage of 70.00%. The data from the questionnaire results were then strengthened by findings during observations and interviews where in the learning process an integration process of digital literacy was carried out in classroom learning through the implementation of an independent curriculum, while the availability of supporting facilities was still very minimal, this was in line with the results of the research questionnaire.